Love Magic and Political Morality in Central Madagascar, 1875-1990 - Graeber, David (Cadernos de Campo (São Paulo, 1991), 2023)
Essay about the "love magic" initially attributed to women users and then to masculine users and how its use and significance are linked to the French colonial occupation in Madagascar.